Automatic programmable air ozonizer - Gubarev, S.P.; Klosovsky, A.V.; Opaleva, G.P.; Taran, V.S.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2015)
In this paper we describe a compact, economical, easy to manage auto air ozonator developed at the Institute of Plasma Physics of the NSC KIPT. It is designed for sanitation, disinfection of premises and cleaning the air from foreign odors. A distinctive feature of the developed device is the generation of a given concentration of ozone, approximately 0.7 maximum allowable concentration (MAC), and automatic maintenance of a specified level. This allows people to be inside the processed premises during operation. The microprocessor controller to control the operation of the ozonator was developed.